The rise of political Islam in Turkey : urban poverty, grassroots activism and Islamic fundamentalism - Delibas, Kayhan (London : I. B. Tauris, 2015)
Turkey, officially a secular state, voted in an Islamist party in 2002 and 2007. How far does this reflect the trend which has seen the rise of political Islam across the Middle East? Does this indicate a growing tendency in the direction of Islamisation amongst the Turkish population? If not, what are the underlying reasons behind the electoral triumphs of the Islamist Justice and Development Party (the AKP)? Kayhan Delibas seeks to answer these questions through an in-depth examination of the appeal of this political party, exploring its ideology, the routes and motives which produce party activists and local party organisations. Concluding that the AKP's success has been built on its criticism of growing inequalities, widespread corruption, unemployment, poverty and lack of basic services, Delibas draws a nuanced portrait of modern Turkish society and the relationship between religion and politics.
Political Islam in Turkey: Grassroots activists and their effect on the rise of Pro-Islamic parties -- The decline of the Turkish political party system, 1980-2002 -- From movement to political party : the changing contours of political Islam in Turkey -- The urban roots of political Islam -- Explaining the meaning of party membership: Routes to and reasons for party membership -- The grassroots activists: The making of Islamist activism -- Not like any other party: The effects of grassroots activism on the electoral outcome -- Conclusion: Fundamentalism demystified
Includes bibliographical references and index : page 315-344
Keywords: AK Parti (Turkey) -- History; Islam and politics -- Turkey; Islam and social problems -- Turkey; Urban poor -- Government policy -- Turkey; Turkey -- Politics and government -- 1980-